Introduction - Kolehmainen Marjo; Lahti Annukka; Lahad Kinneret (Manchester University Press, 2022)
The introduction of Affective intimacies lays out a novel terrain for rethinking intimacies through the lens of affect theories. The questions posed at the outset are set to promote an inquiry into the ways affect studies enrich contemporary theorisations of intimacy. Affective intimacies thus makes an effort to renew the prevailing scholarship and the imaginings of affective intimacies. By doing so, it points to an interdisciplinary lacuna and argues that the social sciences and humanities have yet to recognise affect and intimacy as conjoined processes. More specifically, it is suggested that instead of foregrounding affects and intimacies as pre-defined categories, scholarship would benefit from seeing affect and intimacy as entangled and meshed together. This line of inquiry includes encounters between humans as well as between human and non-human bodies. It thus provides key signposts for comprehending affective intimacies in new ways. The open-ended use of intimacy offers a situated analysis of affective intimacies. From this vantage point, proximity and closeness are not neutral practices but can be imbued with power. Rather than pointing to intimacy as an always positive and desirable closeness, the affective prism prompts us to consider new perspectives on the intimate as it is sensed, lived and entangled across human and non-human bodies. Lastly, the introduction closes with presenting the three sections of the book: the importance of re-imagining affective intimacies, the politics of affect and the queering of intimacies.
Affective Intimacies